2021
DOI: 10.1088/2515-7655/abe424
|View full text |Cite
|
Sign up to set email alerts
|

Modification of TiO2 with metal chalcogenide nanoclusters for hydrogen evolution

Abstract: Using density functional theory, corrected for on-site Coulomb interactions (DFT + U), we have investigated surface modification of TiO2 with metal chalcogenide nanoclusters for hydrogen evolution. The nanoclusters have composition M4X4 (M = Sn, Zn; X = S, Se) and are adsorbed at the rutile (110) surface. The nanoclusters adsorb exothermically, with adsorption energies in the range −2.8 eV to −2.5 eV. Computed density of states (DOS) plots show that cluster-derived states extend into the band-gap of the rutile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…It is easy to recombine, so that the quantum efficiency becomes very low, thereby affecting the photocatalytic efficiency. In order to improve the photocatalytic activity of TiO 2 , a lot of studies have been carried out on the modification of TiO 2 [109–114] . This section briefly introduces metal doping, non‐metal element modification, recombination of TiO 2 with other semiconductors, and multi‐component co‐doping.…”
Section: Modification Principle and Methods Of Tio2‐based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to recombine, so that the quantum efficiency becomes very low, thereby affecting the photocatalytic efficiency. In order to improve the photocatalytic activity of TiO 2 , a lot of studies have been carried out on the modification of TiO 2 [109–114] . This section briefly introduces metal doping, non‐metal element modification, recombination of TiO 2 with other semiconductors, and multi‐component co‐doping.…”
Section: Modification Principle and Methods Of Tio2‐based Nanomaterialsmentioning
confidence: 99%
“…In order to improve the photocatalytic activity of TiO 2 , a lot of studies have been carried out on the modification of TiO 2 . [109][110][111][112][113][114] This section briefly introduces metal doping, non-metal element modification, recombination of TiO 2 with other semiconductors, and multicomponent co-doping.…”
Section: Modification Principle and Methods Of Tio 2 -Based Nanomater...mentioning
confidence: 99%
“…The free energy of H adsorption can be used to assess the performance of the HER. Adsorption of H at nanocluster (S, Se) and surface (O) sites is taken into consideration by Rhatigan et al in the study of M 4 X 4 (M = Sn, Zn; X = S, Se) doped rutile (110) surface 189 . The results indicate that the sulfide modifiers are more active toward HER than the selenide modifiers and exhibit hydrogen adsorption free energies in the active range for most coverages of H. Zhuang et al 183 demonstrated that the active site of HER in Ni n supported TiO 2 (101) and (001) surfaces is the O 2c atoms binding near the Ni n cluster, and the loaded Ni n clusters significantly reduce the HER Gibbs free energy when compared to clean surfaces.…”
Section: The Adsorption Activation and Reaction Of Small Inorganic Mo...mentioning
confidence: 99%